GENDER AND FINANCIAL INCLUSION – A REVIEW OF EXISTING LITERATURE - P, Kowsick. N; K, Ramasamy (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This critical review inspect the effect of gender on financial inclusion by synthesizing current literature. The review aims to understand how gender inequities affect availability to financial resources, financial literacy, and economic development. A systematic approach was employed by analyzing peer-reviewed journals, conference papers, and reputable reports. The review qualitatively assesses the financial inclusion's reach, usage, and outcomes across socio-economic contexts, focusing on empirical studies with robust data on metrics like account ownership, transaction volumes, and access to credit, with an emphasis on gender differences Findings The data shows that there is a gender inequity in financial inclusion. Women often face prominent problems to accessing financial services compared to men. The literature reveals that while mobile banking and other digital financial services have the potential to bridge the gender gap, challenges such as technological literacy, cultural norms, and regulatory barriers persist. Practical Implications Policymakers and financial institutions should create inclusive financial policies for women by enhancing financial literacy, offering gender-sensitive products, and overcoming cultural and regulatory barriers. Tailored solutions to women's specific challenges can boost financial inclusion and contribute to economic development. Originality This review expands current insights body of knowledge by giving a detailed assessment of the latest literature on gender and financial inclusion. It highlights the nuanced influence of financial inclusion initiatives across different regions and demographic groups, offering valuable insights for future research and policy development.